UPAYA PENINGKATAN MINAT BELAJAR PESERTA DIDIK PADA PELAJARAN BAHASA INDONESIA KELAS 1 SD MELALUI PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA UMANG - Amalina Devi; Joko Suliyanto; Partiyah, Partiyah; Rasiman, Rasiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Every student has uniqueness and diversity. Learning should meet the needs of learners for their diversity. However, the learning that is often applied today is conventional learning. This makes students' interest in learning very low. This study aims to increase the learning interest of class I B students at SDN Palebon 03 Semarang in Indonesian Language Lessons. This research is Classroom Action Research (CAR) with 29 students as subjects. This research was conducted in 2 cycles. Collection of information on students' learning interests in this study through questionnaires, observations and interviews. The results of this study are that the student learning interest questionnaire increased from 24,75% to 57% in cycle 1 and 82,75% in cycle 2. Meanwhile, the results of observations and interviews showed an increase in students' interest in learning in each indicator of feelings of pleasure, student involvement, interest, and student attention. Based on this study, can be concluded that differentiated learning assisted by Umang Media can increase students' interest in learning.